2019
DOI: 10.24085/jsaa.v7i1.3693
|View full text |Cite
|
Sign up to set email alerts
|

Theorising the #MustFall Student Movements in Contemporary South African Higher Education: A Social Justice Perspective

Abstract: A significant amount of literature on the student movement in South Africa is characterised by two limitations. Firstly, a significant amount of this literature is found in un-academic and non-peer-reviewed sources, such as social media, online newspapers, blog posts and other platforms. Secondly, some of this literature is characterised by an absence of theory in offering us critical analysis of the emergent conditions of the student movement as a phenomenon in South African higher education (SAHE). In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The second purpose of education is 'socialisation', where education also concerns the hidden and implicit induction of students into the norms, values, and beliefs of a particular society. This alignment of education with the social, economic and political orders reflects Bourdieu's (2011) notion of cultural capital, where students gain access to the official and recognised habitus that they will need to negotiate beyond the family and religious community 2019a;2019b). The third purpose of education for Biesta (2009) is what she refers to as 'subjectification', which largely concerns students becoming independent in their thinking, being, and acting.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The second purpose of education is 'socialisation', where education also concerns the hidden and implicit induction of students into the norms, values, and beliefs of a particular society. This alignment of education with the social, economic and political orders reflects Bourdieu's (2011) notion of cultural capital, where students gain access to the official and recognised habitus that they will need to negotiate beyond the family and religious community 2019a;2019b). The third purpose of education for Biesta (2009) is what she refers to as 'subjectification', which largely concerns students becoming independent in their thinking, being, and acting.…”
mentioning
confidence: 85%
“…This online teaching and learning regime align with the state sanctioned, World Economic Forum developed, discourse of President Cyril Ramaphosa 4 regarding South Africa needing to embrace the 'fourth industrial revolution' and its online pedagogies. This includes acknowledging the plight of the Black working class students located in the township and rural areas who would struggle with access to data, requisite electronic devices, shelter, food, a conducive environment, and training to handle the pressures and demands of online teaching and learning (Heffernan, Nieftagodien, Ndlovu & Peterson 2016;Hlalele 2012;Hlatshwayo & Fomunyam 2019a). Failure to respond to the above, will result in the reinforcement of inequality of the educational experience between middle to upper class students (who will be able to successfully participate in online pedagogies), and those who are still structurally trapped in the township and rural areas (who will continue to struggle to navigate online teaching and learning).…”
Section: Teaching Learning and The Pandemicmentioning
confidence: 99%
“…(Sanchez, 2018, pp. 3-4) In the South African context, the calls for decolonising and transforming 2 curricula have often suggested that the post-1994 political dispensation did very little to challenge or interrupt colonial and apartheid epistemic traditions, and bring about new and inclusive knowledges in curricula (Heleta, 2018;Hlatshwayo & Fomunyam, 2019a;Hlatshwayo & Shawa, 2020). The 1990s and early 2000s were shaped and informed largely by a policy framework that sought to open the doors of higher education to all, especially for the millions 2 While there are new and emergent debates in South African higher education on the differences between transformation (which is seen as reforming the system) and decolonization (which is seen as overhauling and restructuring the system), in this paper we have adopted and operationalized both transformation and decolonization as being concerned with changing the system and attempting to make it socially just and inclusive.…”
Section: Transforming Curricula: Struggles Tensions Alienationmentioning
confidence: 99%
“…This was significant in that it moved beyond the narrow and nativist conception of Africanisation which essentialises and simplifies what it means to be a political African subject (see Msila and Gumbo, 2016). The student movements called for a broader understanding of transforming curricula beyond precolonial, nativist, monolithic, and indigenous conceptions of Blackness (see Hlatshwayo & Fomunyam, 2019a;Naicker, 2016;Ngcobozi, 2015).…”
Section: Transforming Curricula: Struggles Tensions Alienationmentioning
confidence: 99%
See 1 more Smart Citation